Cyber Terorisme dan Eksistensi Gerakan Terorisme Kelompok Islam Radikal di Indonesia - Rochmawati, Ida (Ali Muchasan, 2016)
A new wave in the terrorist movement in the modern era is marked by so incessant by Cyberterorisme. The Power of terrorism shifted to cyberspace to influence, recruit, plan, build communication even launched a campaign of cyberspace. This article seeks to analyze how the actual cyber-terrorism has a tremendous impact on the existence and the diversion of resources to the movements of radical groups in Indonesia. Given the power of the radical movement that led to the terror today has disintegrated and is no longer intact as a massive organized movement, then the virtual world be a promising alternative for building strength back.